Simulated consultations: a sociolinguistic perspective - Atkins, Sarah; Roberts, Celia; Hawthorne, Kamila; Greenhalgh, Trisha (BioMed Central, 2016)
Background Assessment of consulting skills using simulated patients is widespread in medical education. Most research into such assessment is sited in a statistical paradigm that focuses on psychometric properties or replicability of such tests. Equally important, but less researched, is the question of how far consultations with simulated patients reflect real clinical encounters – for which sociolinguistics, defined as the study of language in its socio-cultural context, provides a helpful analytic lens.